Extended Posterior Auricular Artery Flap for Temporo-Parietal Scalp Defect in Previously Irradiated Scalp. Issue 3 (May 2016) - Jadhav, Chandan; Rawlins, Jeremy
Abstract : Background: Temperoparietal scalp defects are fairly common resulting from varied array of etiology. Various reconstructive options exisit, but the aim was to achieve a reliable and simple solution keeping in mind the principle of replacing "like with like." Methods: The authors present a 83-year-old lady who had a fall at her home and was lying unconscious for quite some time on her right side of her temple, leading to full thickness necrosis of overlying scalp. She had received surgery and prior radiotherapy for her basal cell carcinoma of the scalp at the same site of her present injury. She was treated with single stage debridement and reconstruction using extended posterior auricalar artery flap. She had no issues with wound healing. Discussion: Extended posterior auricular artery flap for tempero-parietal scalp defects is a reliable local option as it has the several advantages over the traditional scalp flaps. It preserves the direction of hair follicles, no long scalping incisions, no unsightly dog ears, no need for donor area grafts. In this scenario, the robustness of this flap was truly tested as it was raised from a previously irradiated site and did not have any issues of necrosis. To the best of our knowledge, this is the first report confirming the safety of this reliable local option postirradiation.